Disease detection system of mango leaves - Islam, Sabrina; Paul, Apurba; Chowdhury, Oishe Roy; Fiza, Fahmida Akhter (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.